The prevalence, clinical and epidemiological significance of rare genotypes of M. tuberculosis isolated from tuberculosis patients in Saratov Region - T. Yu. Salina; T. I. Morozova (Туберкулез и болезни лёгких)
The objective: to identify the role, clinical and epidemiological significance of rare genotypes of M. tuberculosis (MTB) in the epidemiology of tuberculosis in Saratov Region.Materials. The spoligotyping and hybridization method by the Spoligo-biochip kit (BIOCHIP-IMB OOO, Moscow) was used to examine sputum samples of 353 patients with newly diagnosed pulmonary TB, who were permanent residents of 20 cities and districts of Saratov Region.Results. MTB population circulating in the examined TB patients was heterogeneous and represented by 13 genotypes (Beijing, Beijing-like, Haarlem, Ural, LAM, T, Manu, Microti, Rus 1, Cas, EAI, Canetti, AFRI). Rare genotypes (EAI, Manu, Microti, Rus 1, Cas, AFRI, Canetti) were found in 42/353 (11.9%) patients, of which EAI genotype was found in 8 patients (2.3%), Manu in 14 ( 3.9%), Microti - 13 (3.7%), Cas - 2 (0.57%), Rus 1 - 1 (0.28%), Canetti - 3 (0.85%) , and AFRI - in 1 (0.28%). Tuberculosis cases caused by the Microti genotype were endemic and characterized by homogeneity of the revealed spoligotypes (SIT 539). Isolates of the Manu genotype were registered only in men (100%), mainly living in rural areas (71.4%) and were characterized by a high heterogeneity of SIT (1195, 1485, 1460, 1482, 1088). Tuberculosis caused by the EAI genotype was characterized by a smaller number of destructive forms and forms with bacterial excretion, and high SIT heterogeneity (300, 1431, 1428, 924, 622, 192). There were single cases of the Cas, Canetti, and R genotypes.